Factor VIII Arg2304 → His Binds to Phosphatidylserine and Is a Functional Cofactor in the Factor X-ase Complex - Lewis, Deborah A.; Moore, Karen D.; Ortel, Thomas L. (Thrombosis and Haemostasis, 2001)
Four factor VIII light chain constructs containing hemophilia A mutations at R2304 and R2307 were prepared and expressed in mammalian cells. These mutations are located in a putative phosphatidylserine binding site identified by peptide studies (spanning amino acids 2303-2332). The levels of all four mutants in conditioned medium were significantly less than wild type by immunoprecipitation and ELISA. R2304H and wild type factor VIII light chains were concentrated by cation exchange chromatography from medium. R2304H and wild type factor VIII light chains bound immobilized phosphatidylserine similarly. The reconstituted cofactor activity of R2304H factor VIII light chain was slightly greater than wild type factor VIII light chain. These results are consistent with the recently reported crystal structure of factor VIII C2 domain that suggests R2304H is not directly involved in phospholipid binding. The observed clinical phenotype is probably due to decreased circulating levels of a functional protein.
Keywords: Factor VIII; factor VIII light chain; hemophilia; phospholipid binding